Problems of the Online-Based Curriculum of Language Learning in Higher Education in the post-Pandemic - Samsu Armadi (Script Journal: Journal of Linguistics and English Teaching, 2022)
Background: Universities must design post-pandemic online learning strategies and pay attention to the characteristics of students and lecturers in their learning. The learning process in higher education is also expected not only to hone students' abilities academically or vocationally but also to be able to produce students who have digital skills. Methodology: The method used in this study is the Confirmatory Factor Analysis method with 135 respondents and analyzed using the Structural Equation Model using Lisrel. Findings: The research findings illustrate that all the independent factors studied to determine the success of learning Indonesian. Conclusion: This research recommends that stakeholders are expected to evaluate the obstacles or obstacles faced so that all online learning activities innovate by producing better learning applications. For further research, it is advisable to use a mixed-method approach to triangulate the results using quantitative and qualitative methods and use a wider sample so that the results can be more generalized. Originality: This study examines post-pandemic language learning, as opposed to online language learning mentioned in earlier research. This research focuses mostly on significant topics such internet network, infrastructure, and lecturer quality.